Clinical functioning information tool – coronavirus disease 2019 (ClinFIT COVID-19): psychometric evaluation and development of an interval-scaled functioning score across the care continuum - Masahiko Mukaino; Catarina Aguiar Branco; Alia Alghwiri; Sonia Amato; Antonios Kontaxakis; Mihai Berteanu; Hüma Bölük Şenlikci; Pinar Borman; Salmane Diouane; Maryam Fourtassi; Francesca Gimigliano; Abderrazak Hajjioui; et al. (Journal of Rehabilitation Medicine)
Objective: to report on the development and global testing of the COVID-19 version of the International Classification of Functioning, Disability and Health-based Clinical Functioning Information Tool called “ClinFIT COVID-19” to collect functioning data of rehabilitation patients across the care continuum to establish an interval-scaled functioning score.